Tradisi Mappatamma' pada Masyarakat Desa Julumate'ne Kecamatan Bontolempangan Kabupaten Gowa (Stuudi Unsur-unsur Budaya Islam) - Ummul Fadilah; Susmihara; Nuraeni S (Al-Hikmah Journal for Religious Studies, 2024)
This study aims to examine the elements of Islamic culture within the mappatamma’tradition in the Julumate'ne Village community, Bontolempangan District, Gowa Regency. The appreciation of the procedure for completing the Qur'an is a compelling subject of discussion, given that the Qur'an serves as a fundamental guideline for Muslims. This research employs a cultural approach, utilizing qualitative data gathered from field studies and literature. To trace this data source, the researcher implemented techniques such as observation, interviews, and documentation. The research methodology is descriptive, providing a detailed account of the characteristics of the research object. The findings indicate that the mappatamma’tradition emerged as a result of the efforts to promote Islam in South Sulawesi and reflects the creativity of the Muslim community, particularly the Bugis-Makassar, in deeply embedding Islamic principles within society. The mappatamma’tradition is executed in three stages: pre-implementation, implementation, and post-implementation. Rich in meaning and conveying messages that embody the community's value system, the mappatamma’tradition encompasses various Islamic values, including religious, social, educational, and scientific dimensions that are essential to uphold and perpetuate in contemporary life.